Comparison of biochar and Poultry Litter Treatment (PLT) amendments on broiler litter quality and bird performance - Maryam K. Mohammadi-Aragh; Katie L. Norris; Gary D. Chesser, Jr.; John W. Lowe; Jeffrey D. Evans; Joseph L. Purswell; John E. Linhoss (Journal of Applied Poultry Research)
SUMMARY: Broiler litter management is critical for overall bird health and performance. Poor litter conditions can result in increased ammonia (NH3) volatilization and moisture, which negatively impact bird productivity and welfare. Poultry Litter Treatment® (PLT) is a litter amendment that has been applied to reduce ammonia (NH3) volatilization; however, PLT does not address litter moisture content (MC). Biochar (BC) is a porous material with a high surface area that may absorb moisture and mitigate NH3 volatilization. The objectives of this study were to evaluate the effects of BC and PLT on MC, NH3 volatilization, and broiler performance during a 42-day flock grow-out. Birds were reared in 1.52 m x 2.74 m pens containing used litter, feeders, and a drinker line. Water activity, pH, and nutrient content were also evaluated. PLT and BC were surface applied at 0.73 kg∙m-2 and 30 % (vol/vol). A control of non-amended litter was included. Litter samples were collected at d 0, 17, 29, and 41. NH3 was measured on d 0, 14, 28, and 41. Litter treatment and grow-out time significantly impacted NH3 volatilization and MC. Overall, PLT had the lowest NH3 concentrations. On d 41, BC had the highest NH3 (104 ppm). BC-treated litter had the lowest MC and highest NH3, while PLT-treated litter was lowest in NH3 volatilization. Litter treatment had no effect on bird performance, indicating these amendments did not negatively affect bird performance. BC may promote lower MC; however, further research is needed to understand its effects on NH3 volatilization.